Place marketing applied to the city of Marseille - Mustafa, Fulden; Zárybnická Žárová, Marcela, 1959-; Kervyn, Nicolas; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
The purpose of this master’s thesis is to examine which place marketing strategies can be applied to the city of Marseille to attract visitors and enhance its image. The city faces the challenge of a long-term image crisis due to several past events. Using a between-subject experimental approach with a sample of 327 people, we tested four conditions: two place marketing strategies from the multi-step model for altering place image developed by Avraham and Ketter, one Phoenix tourism condition, and a control condition. Our findings indicate that none of the studied strategies would be universally effective; however, the message strategy of delivering a counter-message to the stereotype is most effective for those who have already visited the city. Therefore, we recommend continuing to test additional taglines to find the most effective one to integrate into the city’s plan for 2024-2030.
Vedoucí práce: Marcela Zárybnická Žárová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses